Alandra's lilacs - Bowers, Tressa, 1949- (Gallaudet University Press, 1999)
The hearing mother of a deaf child recounts her experiences and provides advice for other parents in a similar situation. Author tells of her 25-year struggle through divorce, poverty, & intractable physicians & educators to raise Alandra her deaf daughter, & the bond she now has with her deaf grandchildren.